PENGARUH PELATIHAN, PENEMPATAN DAN PENGAWASAN TERHADAP KINERJA PEGAWAI DINAS PERINDUSTRIAN DAN PERDAGANGAN PROVINSI RIAU - Karman, Rano; Indarti, Sri (Jurnal Tepak Manajemen Bisnis, 2017)
This research was aimed to find out and analyze the effects of training, work placement, and monitoring toward the employeesâ performance at the department of industry and commerce, Riau Province. The research method in this research was quantitative method. Type and data source were primary data obtained from the result of empirical research by distributing the questionnaires to the employees sampled. Data analysis technique used was multiple linear regression. The results of the research show that (1) trainings do not have effects on the employeesâ performance of the department of industry and commerce. Nevertheless, the results of data analysis show a positive value. This indicates that the contribution of training factor towards the employeesâ performance was low and unable to improve the performance significantly. This is because when the trainings were given to the employees, some of them did not take the trainings seriously. Therefore, training implementations given to the employees were not optimal to affect the employeesâ work performance. (2) Work placement has positive and significant effects toward the employeesâ performance of the department of industry and commerce, Riau province. The placement of employees based on their areas of expertise surely gives the positive effects towards the employeesâ performance. (3) Monitoring has positive and significant effects toward the employeesâ performance of the department of industry and commerce, Riau province. Monitoring the employees intensively will help them in doing their work and direct them in maximizing their work result that will result in their work improvement. (4) Training, work placement, and monitoring simultaneously have significant effects toward the employeesâ performance of the department of industry and commerce, Riau province.